A note on how NK landscapes work - Felipe A. Csaszar (Journal of Organization Design, 2018)
The NK landscape methodology has been used by much research in strategy and organizations, and the concept of "landscape" has become a popular business idea. Despite such popularity, exactly what NK landscapes are and how they work is typically obscure to all but a small specialist audience. This technical note clarifies the NK landscape methodology by explaining how an NK landscape is computed. This note also discusses ways in which NK landscapes are represented and used in research. The aim of this note is enabling more researchers to engage more deeply with the work that relies on the landscape concept.
Keywords: 650